Private Convex Optimization in General Norms - Gopi, Sivakanth; Lee, Yin Tat; Liu, Daogao; Shen, Rouqi; Tian, Kevin (SODA 2023, 2022)
We propose a new framework for differentially private optimization of convex functions which are Lipschitz in an arbitrary norm via regularized exponential mechanism.